OPTIMALISASI DAYA LISTRIK PADA ALAT AIR BLAST UNTUK MENINGKATKAN EFISIENSI OPERASIONAL LABORATORIUM OTOMASI INDUSTRI - Rabika, Reval Dion; Rongkonusa, Kevin Marcelino; Budiman, Marson James (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Air Blast machine at the Industrial Automation Laboratory of Politeknik Negeri Manado is equipped with two belt conveyors — one horizontal feed conveyor and one inclined discharge conveyor — each driven by a 0.75 kW three-phase induction motor. Under the conventional direct-on-line (DOL) start system, both motors run at constant maximum speed regardless of material load, resulting in unnecessary energy waste, a low system power factor of 0.68, and a high inrush current of 24.8 A at each startup. This study designs and evaluates an Arduino Nano-based control system integrated with a VEIKONG VFD to dynamically regulate conveyor belt speed based on real-time motor current data acquired via PZEM-004T sensors. The system employs a three-tier speed profile: full speed during material loading, reduced speed during processing, and minimum speed during idle periods, all managed autonomously by the Arduino Nano mounted on a NANO aPLC 5.2 expansion board. Measurements were conducted over 30 working days split into two 15-day phases. Daily energy consumption fell from 7.6 kWh to 5.3 kWh (a 30.3% reduction), the system power factor improved from 0.68 to 0.77, reactive power decreased by 45.6%, and the start inrush current dropped from 24.8 A to 7.4 A (a 70.2% reduction). At the laboratory system level, total daily consumption decreased from 18.0 kWh to 15.7 kWh, a 12.7% improvement. Estimated monthly cost savings amount to Rp 73,122, with a project payback period of under 26 months against a total investment of Rp 1,850,000.